Inovasi Perpustakaan Melalui Pemanfaatan Teknologi Augmented Reality Dan Virtual Reality di Era Generasi Z - Aulianto, Dwi Ridho (Nusantara Journal of Information and Library Studies (N-JILS), 2020)
This study aims to determine the benefits of Augmented Reality and Virtual Reality technology applied to libraries in the Z generation era. The research method used study of literature by collecting several reference as sources that are relevant to the study material and and interviews with several generation Z informants. The results of the study found that the implementation of Augmented Reality technology can be used to create and read the Interactive Opac Brochure with AR; Utilization of Library Collection Display; Utilization for Searching Library Collections in Shelves through AR; Utilization for Interactive Learning Media for Users. While the implementation of Virtual Reality technology can be used for tours or library tours; Library Services; Information Literacy and Online Catalog.